Publishing as a Creative Industry - Marsden, Stevie (Routledge research in the creative and cultural industries., 2025)
Book publishing is big business, contributing significant employment in the creative industries and adding billions to the global economy. Despite this, the sector is often overlooked in the creative industries' research tide. This book remedies this gap in knowledge, providing an examination of book publishing in the UK within the wider context of the creative industries and the existing academic discourse.Balancing the tensions of art and commerce perhaps more than any other creative field, this book considers the position of the book publishing industry within the contemporary cultural economy. Through this focused analysis on the culture(s) and organisation(s) of book publishing in the UK, the author demonstrates how this creative industry reflects, and perpetuates, many of the key issues and challenges, including inequalities in representation, cultural and economic dominance of global conglomerates, and hierarchies of value, already recognised as central within the creative industries in the UK and beyond.This concise book will be essential reading for academics, researchers, and students with an interest in the publishing industry and its position within the UK Creative Industries and cultural economy.